The Impacts of Drug Abuse Across Individual, Family and Societal Dimensions (Sukuna Journal, 2026)
Drug addiction is a serious issue that affects not only individuals but also their families and society. This study aims to understand how drug addiction influences people’s lives and their relationships with family, relatives, and others. The researcher spoke with 10 individuals from different age groups who are residing in two rehabilitation centers in Morang, Nepal. The researcher also spoke with two individuals who have completed their treatment and are now struggling to return to a normal life. Simple questions were asked to understand their experiences, challenges, and feelings. The findings reveal that most people start using drugs as teenagers, mainly due to peer influence. Many of them dropped their studies and got involved in harmful activities such as borrowing money from others and selling valuable household items to manage money for drugs. All participants expressed their regret for their past activities, acknowledging that their addiction caused emotional pain, financial problems, and loss of trust within their families and relatives. They also faced difficulties adjusting back into their society. The study clearly shows that drug addiction negatively affects their personal life, education, family relationships, and future opportunities. The study also reveals that the whole community should work together to protect young people, so they do not fall into the world of drug addiction.